Efficiency estimation of using phased program of caries prevention in children domiciled in Transcarpathian region - Klitynska Oksana V.; Kostenko Yeugenya; Mukhina Yaroslava A.; Vasko Artur A.; Layosh Natalia V. (Medicinski fakultet i Klinika za stomatologiju, Niš, 2016)
Background: Caries is a pathological process that occurs in the hard tissues of the teeth after eruption and reduced quality of life due to significant complications, especially in children. An extremely high incidence of dental caries among children living permanently in Transcarpathian region requires a comprehensive prevention program. The aim of this study was to determine the efficiency of complex caries prevention program among children permanently living in the area of biogeochemical fluorine deficiency. Aim of the study: To evaluate efficiency level of using phased program of caries prevention among children of different age groups domiciled in Transcarpathian region. Material and Methods: On examination of 346 children aged 3-8 years, among which 163 (46.9%) boys and 183 (53.1%) girls, a phased program of complex prophylaxis was created, covering the basic dental diseases in children living permanently in deficiency conditions. The program included: hygienic education of preschool children and their parents; exogenous medicament prevention; early identification and treatment of caries using conventional methods according to treatment protocols; endogenous non-medical prevention, nutrition correction have proved its effectiveness. Results: The indicator of caries prevention efficiency of the proposed scheme for children 5-7 (3-5) years is 69.5%; for children 8-10 age group (6-8) years - 66.9%. Conclusion: The main strategy of pediatric dental services in Ukraine should be created for the children population (aged up 18 years) through national and regional programs for the primary prevention of main dental diseases with providing adequate financing in sufficient volume to preserve the nation's dental health for the next 20 years.